2012
DOI: 10.1007/s13539-012-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia: impact, mechanisms and emerging treatments

Abstract: Many forms of cancer present with a complex metabolic profile characterised by loss of lean body mass known as cancer cachexia. The physical impact of cachexia contributes to decreased patient quality of life, treatment success and survival due to gross alterations in protein metabolism, increased oxidative stress and systemic inflammation. The psychological impact also contributes to decreased quality of life for both patients and their families. Combination therapies that target multiple pathways, such as ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
7

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 201 publications
(323 reference statements)
3
135
0
7
Order By: Relevance
“…But although many researchers and pharmaceutical companies tried to find therapies for muscle atrophy, including cachexia and sarcopenia, no solution has been established until now. 71,99,100 Interestingly, Morley et al discussed if we are closer to having drugs for treatment muscle wasting disease and therefore drugs were highlighted, which showed current advances in therapy for sarcopenia and cachexia (e.g. ghrelin agonists, selective androgen receptor molecules, megestrol acetate, activin receptor antagonists, espindolol, and fast skeletal muscle troponin inhibitors).…”
Section: Current News On Biomarker Researchmentioning
confidence: 99%
“…But although many researchers and pharmaceutical companies tried to find therapies for muscle atrophy, including cachexia and sarcopenia, no solution has been established until now. 71,99,100 Interestingly, Morley et al discussed if we are closer to having drugs for treatment muscle wasting disease and therefore drugs were highlighted, which showed current advances in therapy for sarcopenia and cachexia (e.g. ghrelin agonists, selective androgen receptor molecules, megestrol acetate, activin receptor antagonists, espindolol, and fast skeletal muscle troponin inhibitors).…”
Section: Current News On Biomarker Researchmentioning
confidence: 99%
“…According to this definition, at the World Congress on Osteoporosis, Osteoarthritis and Musculoskeletal Diseases, a research group from the University of Liège (Belgium) revealed dramatic numbers about the prevalence of sarcopenia in Europe, providing also some interesting projections. In 2016, the European citizens affected by sarcopenia there are 10 869 527 (11.1% of older population) and this number will tend to the increase of 72.4%, reaching a total of 18 735 173 sarcopenic people in 2045 (12.9% of older population) (14).…”
Section: Epidemiology Of Sarcopenia and Cancer Cachexiamentioning
confidence: 99%
“…Nonetheless, the development and evaluation of psychosocial, educational, and informational interventions for patients with cachexia and their families and caregivers remain in their infancy. 32 Families often rationalize that if food intake is increased, weight will be regained and survival increased; the failure to increase intake is equated with hastening of death. This stems partially from a lack of communication with families about the nature and causes of wasting in cachexia, as atrophy is caused by factors independent of nutritional or calorific intake, and also from the need to take an active role in treatment, with food preparation being highly symbolic of the need to nurture.…”
Section: Family Support Interventionsmentioning
confidence: 99%